Linkages between government spending, growth, and poverty in rural India - Fan, Shenggen; Hazell, Peter B. R.; Thorat, Sukhadeo (International Food Policy Research Institute, 1999)
India spends more money on agriculture each year than any other developing Asian country. These expenditures (Figure 1) have contributed to the dramatic improvement in the country’s food security situation since the mid-1960s and to a steady decline in the incidence of rural poverty. However, as the government faces increasing pressure to contain its budget deficits, the need becomes imperative to target its spending more efficiently to achieve its growth and poverty alleviation goals. To do so, policymakers must have a clear understanding of how different types of public investment affect agricultural growth and rural poverty.